2008
DOI: 10.1103/physrevb.77.201403
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for the suppression of charge stripes in epitaxialLa1.67Sr0.33NiO4films

Abstract: We have successfully grown epitaxial La1.67Sr0.33NiO4 films with a small crystalline mosaic using pulsed laser deposition. With synchrotron radiation, the x-ray diffraction peaks associated with charge stripes have been successfully observed for relatively thick films. Anomalies due to the charge-ordering transition have been examined using four-point probe resistivity measurements. Xray scattering provides direct evidence for suppression of the stripe phase in thin samples; the phase disappears for film thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…These devices typically require ultra thin films or nanoparticles of materials making the study of size effects of paramount importance to future functionality. For instance, it was found that the bulk CO transition is rapidly suppressed in the nano-limit or under high pressure for CMR manganite systems 12,13 ; while in thin films the CO transition temperature can be suppressed entirely or even increased from the bulk value [14][15][16] . Further, to be technologically viable a device typically needs to operate at room temperature and above, while in complex oxides CO is typically a low temperature phenomenon.…”
mentioning
confidence: 99%
“…These devices typically require ultra thin films or nanoparticles of materials making the study of size effects of paramount importance to future functionality. For instance, it was found that the bulk CO transition is rapidly suppressed in the nano-limit or under high pressure for CMR manganite systems 12,13 ; while in thin films the CO transition temperature can be suppressed entirely or even increased from the bulk value [14][15][16] . Further, to be technologically viable a device typically needs to operate at room temperature and above, while in complex oxides CO is typically a low temperature phenomenon.…”
mentioning
confidence: 99%